A Model of the Process of Women’s Entry into Business Ownership: A Study among Malay Businesswomen in Malaysia (Journal of Governance and Development (JGD), 2012)
More women from western and developed countries enter business ownership and more women in Asia, particularly in Malaysia, are also becoming self-employed despite many tangible and intangible obstacles. In the face of these barriers, they still demonstrate a strong determination to succeed. In view of this, this paper will attempt to present a theoretical model of the economic and social factors associated with Malay businesswomen in the rural environment. Insights into the influence of socio-economic factors on entrepreneurship is based on a study of 31 Malay rural businesswomen from the District of Pendang, Kedah. This study has shown that a combination of individual needs and experience are not the only reasons why women start their own business ventures. In each case, other events and external factors have catapulted the women into business ownership. Hence this paper has set out theoretical and methodological implications that contribute to our knowledge about the theory of the origins of entrepreneurship among rural businesswomen.